Predicting Recurrence and Progression in Non-Muscle-Invasive Bladder Cancer Using European Organization of Research and Treatment of Cancer Risk Tables - Ather, M Hammad; Zaidi, Masooma (Urology Journal, 2009)
Introduction: We determined the recurrence and progression at 1 year in patients with non-muscle-invasive urothelial carcinoma who underwent transurethral resection of bladder tumor (TURBT) and compared those with the calculated risk according to the European Organization of Research and Treatment of Cancer (EORTC). Materials and Methods: Follow-up data of 92 patients with non-muscle-invasive bladder cancer who underwent TURBT were reviewed, and their 1st year recurrence and progression were recorded. The risk of recurrence and progression were calculated for 1 year according to the EORTC scoring system, using tumors’ stage, grade, size, and multiplicity, and the presence of carcinoma in situ and previous recurrence episodes. The outcomes were compared with the EORTC’s predictive scores. Results: The patients were 75 men and 17 women with an age range of 31 to 91 years. Sixteen patients (17.4%) had a recurrent disease, 41 (44.6%) had a tumor larger than 3 cm in diameter, 35 (38.0%) had multiple lesions, 2 (2.2%) had carcinoma in situ, 73 (79.3%) had stage T1 lesions, and 8 (8.7%) had a high-grade disease. Recurrence was found in 34 patients (37.0%). The recurrence rates were 20.0%, 28.2%, 40.5%, and 83.3% in groups with the predicted EORTC risks of 15%, 24%, 38%, and 61%, respectively. There were 2 patients (2.2%) with progression of the diseases. Conclusion: A significant concordance was noted between the EORTC’s calculated risk and the recurrence rate of stage Ta T1 bladder cancer at 1 year. Progression was less than that predicted, probably due to our small sample size.